Selected Decisions (14th Ed). (Selected Decisions, 1989)
This paper proposes for adoption by the Executive Board as guidelines for Committees of the Executive Board when considering the amount of a subscription that should be paid in reserve assets. In applying the guidelines, a Committee shall pay due regard to present and prospective economic and financial circumstances of the country concerned. A reasonable approximation of the amount of the subscription that has been paid in reserve assets in the past is the average of all reserve assets actually paid in terms of the quotas of all members, rather than the proportions paid in the past by individual members. In making the calculation of the reserve assets to be paid, account will be taken of the repurchases made in the past by members, including those made in accordance with Schedule B of the amended Articles, and of sales of the currencies of members made to reduce to that level the amounts of the member's currency paid in excess of 75 percent of quota by a member that had joined the IMF before the date of the Second Amendment.